Pengaruh Pupuk Organik terhadap Serapan Ca dan Mg serta Hasil Kacang Tanah pada Lahan Terdegradasi - Sri Hartati; Hery Widijanto (Agrosains : Jurnal Penelitian Agronomi, 2015)
Degraded land is the land that has lost a lot of nutrients and soil organic matter. This research is aimed to determine the effect of the kinds of organic fertilizers to Ca and Mg uptake and yield of groundnuts on degraded land. This research was done using Completely Randomized Design (CRD) single factor and three replications for each treatment. The results showed that organic fertilizer influence to Ca and Mg uptake and the yield of groundnut on degraded lands. Eichonia crasspies manure increased Ca and Mg uptake of groundnut on degraded soil. Cow manure fertilizer increased 200% of their groundnut production as compared to without organic fertilizer.